The Influence of Teacher Communication Models in Online Learning on Students’ Learning Outcomes - Mursalin, M; Muliana, M; Ali, Muhammad; Febriansyah, Muhammad; Afif, Arriza Maulana (SAINTIS Publishing, 2023)
The aimed of this study was to determined whether there was an influence of the teacher's communication model during online learning on student learning outcomes at SMA Negeri 5 Lhokseumawe. This study uses a quantitative research approach with experimental methods in the form of quasi-experiments. The population of this study were all students of SMA Negeri 5 Lhokseumawe. The sample is students in grades XI-1 and X1-2 in the 2022/2023 academic year. This research was conducted at SMA Negeri 5 Lhokseumawe for the 2022/2023 academic year. Student learning outcomes tests consist of questions in the form of descriptions given after learning. After the data is obtained from the results of the pre-test and post-test, data processing is carried out. Data processing is done based on the problems in this study. Beginning with conducting data analysis prerequisite tests such as homogeneity and normality tests before analyzing the hypothesis using the t-test. Based on the statistical test results it is known that the Asymp. Sig. (2-tailed) of 0.001 0.05, it can be concluded that the hypothesis is accepted. Thus it can be said that there are differences between the Experimental class and the Control class. Because there is a significant difference, it can be said that there is an influence of the teacher's communication model in online learning on student learning outcomes at SMAN 5 Lhokseumawe.